From the Uruguay Round to coloured boxes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A major achievement of the so-called Uruguay Round (the round of world trade negotiations from the mid-1980s to the mid-1990s which led to the formation of the World Trade Organisation) was the Agreement on Agriculture (AoA). The AoA aimed at three...